2021
DOI: 10.3389/fmicb.2021.761282
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus US3 Protein Inhibits IFN-β Production by Interacting With IRF3 to Block Its Activation

Abstract: Pseudorabies virus is a typical swine alphaherpesvirus, which can cause obvious neurological disorders and reproductive failure in pigs. It is capable of evading host antiviral immune response. However, the mechanism by which many PRV proteins assist the virus to evade innate immunity is not fully understood. This study identified PRV US3 protein as a crucial antagonistic viral factor that represses interferon beta (IFN-β) expression. A in-depth study showed that US3 protein restricted type I IFN production by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Many viruses, including herpesviruses have evolved various strategies to suppress apoptosis of infected cells and evade cell-mediated immune response by encoding multiple anti-apoptotic genes. The US3 protein kinase encoded by herpes simplex virus type-1 (HSV-1) or PRV could block apoptosis induced by overexpression pro-apoptotic family members of Bad or Bcl-2 [ 32 , 33 , 34 ]. We also demonstrated that the function of PRV ΔgE/TK/US3 inhibiting infected cell apoptosis is decreased after deletion of US3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses, including herpesviruses have evolved various strategies to suppress apoptosis of infected cells and evade cell-mediated immune response by encoding multiple anti-apoptotic genes. The US3 protein kinase encoded by herpes simplex virus type-1 (HSV-1) or PRV could block apoptosis induced by overexpression pro-apoptotic family members of Bad or Bcl-2 [ 32 , 33 , 34 ]. We also demonstrated that the function of PRV ΔgE/TK/US3 inhibiting infected cell apoptosis is decreased after deletion of US3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid shutdown of interferon production is carried out by viral tegument proteins that are released during entry of the virus and by (immediate) early viral proteins. For example, the UL13 tegument protein kinase of PRV suppresses type I IFN production via degradation of PRDX1, IRF3 and STING ( 30 32 ), the US3 tegument protein kinase of PRV triggers degradation of IRF3 and Bclaf1 to suppress type I IFN production ( 33 , 34 ), and the early EP0 protein of PRV antagonizes type I IFN production by inhibiting IRF9 ( 35 ). Hence, although speculative, we hypothesize that, in comparison with low MOI infection, high MOI PRV infection leads to increased intracellular concentration of incoming tegument viral proteins and increased production of (immediate) early viral proteins, which counteract the type I IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al demonstrated that PRV US3 inhibits IFN-I production by degrading IRF3. The results showed that PRV US3 could inhibit host antiviral innate immunity by targeting various host defense mechanisms [ 56 ]. CREB-binding protein (CBP/p300) is a histone acetyltransferase, which has been proved to play an important role in transcriptional regulation.…”
Section: Prv Infection Inhibits Ifn-i Productionmentioning
confidence: 99%